The Impact of Remittances on Household Consumption and Economic Growth in Jordan - Mashaqbeh, Dr. Hamza Mohammed Daher (International Journal of Accounting and Economics Studies, 2025)
Like any other developing nation, money sending boosts the performance of the economy through providing household income and enhancing economic growth. This research examines the effects of these private capital inflows on the consumer expenditure and economic growth in Jordan; the country where it about 12.5% of the budget share. From the spending behavior, the study established that flexibility of part of the remittances to basic needs like food, shelter, and education lowers poverty levels, besides improving the quality of life. This paper shows that while the increase in consumption outweighs investment, the long-term developmental impact of remittance inflows is constrained. Also, the skewed distribution of the flow of remittances in the urban areas deepens the imbalance of economic development between urban and rural regions. In macro explanatory analysis, remittances have a positive impact on the GDP and a reduction in unemployment levels, and hence are more reliable than FDI or ODA. In this research, the twin effects of the remittance, the positive and the negative are unveiled. The study emphasises the need to design policies that support productive utilisation of the money sent by the workers to their families, educate households about proper usage, and fight for fair distribution to tap the potential for boosting the Jordan economy.